SYNTHESIS, THERMAL BEHAVIOR AND SPECTROSCOPIC INVESTIGATIONS OF METAL COMPLEXES WITH N-MODIFIED GLYCINE AS LIGAND - SACALIS, Carmen; GOGA, Firuţa; DAVID, Leontin (Studia Universitatis Babeș-Bolyai Chemia, 2017)
The Cu(II), Co(II) and Ni(II) complexes with N-modified glycine derived from p-nitrophenylserinol were synthesized and characterized by their spectral and thermal properties. The thermal stability of the ligand and synthesized complexes was discussed in the 20-700oC temperature range. The results indicate that the organic compound acts as a bidentate ligand, its coordination involving the carboxylate oxygen and the nitrogen atom belonging to the amino group of the glycine fragment. All complexes correspond to the molar ratio M : L : H2O = 1 : 2 : 2. The shape of the ESR spectra at room temperature and the principal values of the g tensor suggest a pseudotetrahedral local symmetry around the metal ions.